Intelligent system to detect violations in pedestrian areas committed by vehicles in the City of Cartagena de Indias (LACCEI, 2024)
This article presents applied research which proposes an approach to a low-cost electronic system that allows the detection of violations in pedestrian areas. For this purpose, we proposed an electronic system that implements artificial intelligence algorithms and Internet of Things architectures to detect in real-time these events. The proposal focuses on experimental laboratory work through which we developed and validated a system by analyzing a real pedestrian zone scenario and invasion of the pedestrian zone. As a result of this work, we deliver a labeled dataset to the scientific community that can serve as input to new projects and the development of better offender detection algorithms